A hyperluminous obscured quasar at a redshift of z ≈ 4.3. Issue 1 (1st March 2021) - Efstathiou, Andreas; Małek, Katarzyna; Burgarella, Denis; Hurley, Peter; Oliver, Seb; Buat, Veronique; Shirley, Raphael; Duivenvoorden, Steven; Lesta, Vicky Papadopoulou; Farrah, Duncan; Duncan, Kenneth J; Varillas, María del Carmen Campos
ABSTRACT: In this work we report the discovery of the hyperluminous galaxy HELP_J100156.75 + 022344.7 at a photometric redshift of z ≈ 4.3. The galaxy was discovered in the Cosmological Evolution Survey (COSMOS) field, one of the fields studied by the Herschel Extragalactic Legacy Project (HELP). We present the spectral energy distribution (SED) of the galaxy and fit it with the CYprus models for Galaxies and their NUclear Spectra (CYGNUS) multi-component radiative transfer models. We find that its emission is dominated by an obscured quasar with a predicted total 1–1000 μm luminosity of 3.91^+1.69_-0.55 × 10^13 L_ and an active galactic nucleus (AGN) fraction of 89 per cent . We also fit HELP_J100156.75 + 022344.7 with the cigale(code investigating galaxy emission) code and find a similar result. This is only the second z > 4 hyperluminous obscured quasar discovered to date. The discovery of HELP_J100156.75 + 022344.7 in the ∼2 deg 2 COSMOS field implies that a large number of obscured hyperluminous quasars may lie in the HELP fields, which cover ∼1300 deg 2 . If this is confirmed, tension between supermassive black hole evolution models and observations will be alleviated. We estimate the space density of objects like HELP_J100156.75 + 022344.7 at z ≈ 4.5 to be ∼1.8 × 10 −8 Mpc −3 . This is slightly higher than the space density of coeval hyperluminous optically selected quasars, suggesting that the obscuring torus in z > 4 quasars may have a covering factor 50 per cent .